Literature Study of Fixed Asset Depreciation Calculation On Profit In Financial Statements - Juliarta Elisabeth Silitonga; Dona Olivia Sihombing; Talitha Nabila; Muhammad Khoiri Luthfi; Nur Aliah (Journal of Indonesian Management, 2024)
Depreciation of fixed assets is an important element of accounting that has a significant impact on financial reporting, especially profit reporting. The purpose of this study is to analyze the calculation of depreciation of fixed assets and its impact on reported profit. Consider different depreciation methods, such as the straight-line method, declining balance method, and production unit method, to understand how each method affects cost allocation and income statement results. In addition, this study also discusses the relevance of Statement of Financial Accounting Standards (PSAK) no. 16 Shows the effect of recognizing depreciation expense and tax obligations due to the recognition of depreciation expense. The results of the analysis show that choosing the right depreciation method not only affects net income, but also plays an important role in asset management and corporate strategic decision-making. Therefore, an in-depth understanding of fixed asset depreciation is essential for managers to develop investment strategies and comply with accounting standards.